Empire of the sum : the rise and reign of the pocket calculator - Houston, Keith, 1977- (W.W. Norton & Company, 2023)
"The hidden history of the pocket calculator -- a device that ushered in modern mathematics, helped build the atomic bomb, and went with us to the moon -- and the mathematicians, designers, and inventors who brought it to life." -- back cover